A combination of approaches evidenced seed storage behaviour in the miracle berry Synsepalum dulcificum (Schumach. et Thonn.) Daniell - Tchokponhoué, Dèdéou Apocalypse; N’Danikou, Sognigbé; Achigan-Dako, Enoch Gbenato (My University, 2019)
Background: Knowledge on seed storage behaviour is crucial for planning conservation strategies of plant genetic resources particularly in economically promising but endangered species like Synsepalum dulcificum, viewed as recalcitrant-seeded species albeit sound evidence was lacking. In this study, we combined an experimental approach based on critical moisture content and storage environment analysis, and the seed-coat ratio–seed dry mass (SCR-SM) model to clarify the seed storage behaviour in the species. Seed moisture content at shedding was determined and effects of dehydration and cold storage on seed viability, germination and subsequent seedling vigour were analysed. The probability for dessication-senstivity [P(D-S)] was also determined. Results: Our findings indicated that S. dulcificum seed moisture content at shedding was 36.60% with nearly 100% viability. Seed dehydration below 20% moisture content induced a total loss of viability whereas low temperature storage (at 10 °C or 4 °C reduced shelf life to a maximum of 7 days. More importantly, S. dulcificum seed storage at 0 °C was highly detrimental and resulted in a total loss of viability whatever the storage duration. Only a storage at 25 °C helped expand the shelf life to 28 days. However, at 28 days storage the viability was extremely low with almost no germination. The probability for dessication-senstivity P(D-S) in the species is largely greater than 0.5. Seed dehydration and storage environment highly affected subsequent germination rate and seedling vigour. While dehydration improved seedling performance storage at low temperature rather inhibited seedling growth. Conclusion: Taken together, these findings are the first to set evidence of recalcitrance in S. dulcificum and serve hands-on information for practical handling of the seeds and designing sustainable conservation practices for adequate future breeding programme in the species
Keywords: Richardella dulcifica; Recalcitrance; Seedling growth; Sustainable conservation